Pengembangan Perangkat Pembelajaran Pada Materi Usaha dan Energi Berbasis Project Based Learning - Isnaini, Rahasti; Gunawan, Gunawan; Taufik, Muhammad (Mataram University, 2021)
Â This study aimed to develop learning tools on business and energy materials based on project based learning models that are suitable for use in learning. This research was a development research by 4Ddevelopment model design consisting of 4 stages, namely: define; design, develop, and disseminate. This research was only up to the stage of development. Based on the results of validation by experts, the development of learning tools in this study was valid. The percentage of validity was 87.5% on the syllabus; 87.5% on the lesson plan implementation; and 82.5% on student worksheets. Based on the results, the development of learning tools in this study is feasible to use with revisions to the student worksheet because it has quite valid criteria.